Mos 2013 study guide for Microsoft Access - Pierce, John 1954- (Microsoft Press, 2013)
Designed to help you practice and prepare for the 2013 Access Microsoft Office Specialist (MOS) exam, this all-in-one study guide features: full, objective-by-objective exam coverage; easy-to-follow procedures and illustrations to review essential skills; hands-on practice tasks to apply what you've learned; includes downloadable practice files. --
Print version record
Keywords: Microsoft Access; Business -- Study guides -- Computer programs -- Examinations; Microsoft software -- Study guides -- Examinations; Logiciels Microsoft; Examens; Guides de l'étudiant; COMPUTERS; Programming Languages; SQL; Business; Computer programs; Examinations; Microsoft software; Examinations; Study guides